Deiksis Persona dalam Tajuk Rencana Surat Kabar Kompas Edisi November 2015 dan Implikasinya Terhadap Pembelajaran Bahasa Indonesia Kurikulum 2013 - Lestariningsih, Umi, Drs. yakub Nasucha, M.Hum (2017)
This study aimed to describe the form and meaning of deixis persona in the editorial column of the newspaper Kompas November 2015, and the implications of deixis persona against Indonesian language learning in high school curriculum, 2013. The method used in this research is descriptive qualitative method. The data in this study is the editorial. Sources of data in this research is the newspaper Kompas November 2015. Data collection technique used is the method see note technique. Methods refer to the use of language in writing, and then record the necessary data. The results were obtained based on the formulation of the problem include (1) Describe the form of deixis persona in an editorial the newspaper Kompas November 2015, (2) Describe the meaning of deixis persona on the editorial newspaper Kompas November 2015, and (3) Describe the implications deixis persona the Indonesian language learning curriculum, 2013. Based on the analysis, it is known that the data obtained in the editorial column of the newspaper Kompas November 2015 a number of Form 60. the first person deixis numbered 44, namely first person singular pronoun No 1 data and pronoun persona first plural there are 43 data. The second form of deixis persona there is only 1 data, that second person singular pronoun there first data and second person plural pronoun is not found. The third form of deixis persona totaled 15, which is the third person singular pronoun there are 11 data and the third person plural pronoun there are 4 data. Deixis persona that exist in the newspaper Kompas November 2015 can be implicated in learning Indonesian in the high school curriculum in 2013.